A New, Simple, and High-Yielding Synthesis of 2,9-Dihydro-1H-pyrido[3,4-b]indol-1-ones - La Regina, Giuseppe; Famiglini, Valeria; Passacantilli, Sara; Pelliccia, Sveva; Punzi, Pasqualina; Silvestri, Romano (Synthesis, 2014)
A new, simple, and high-yielding method was developed to prepare 2,9-dihydro-1H-pyrido[3,4-b]indol-1-ones by selective cyclization of the appropriate N-(2,2-dimethoxyethyl)-1H-indole-2-carboxamide in polyphosphoric acid at 110 °C for 30 minutes. The reaction yield was strongly dependent on the acid used. The method was less affected by the presence of electron-donating and -withdrawing substituents at 5-position of the indole nucleus.
Keywords: β-carbolinones; β-carboline; polyphosphoric acid; cyclization; heterocycles